y∈f(S)∪f(T)⟹∃x∈(S∪T)s.t.f(x)=y
x∈(S∪T)⟹y=f(x)∈f(S)∧y=f(x)∈f(T)
y=f(x)∈f(S∪T)⟹f(S)∪f(T)⊂f(S∪T)
Ok, I don't have the intuition to prove things like this, so what can I do to develop that intuition?
I don't even really understand what I wrote.
Answer
The very first thing that I recommend is that you use more words and fewer symbols: it’s much easier to be clear on the logic if you explain it verbally as you go.
You have a function f:X→Y, say, and you want to show that if S,T⊆X, then f[S]∪f[T]⊆f[S∪T].
The most straightforward approach will work nicely: start with an arbitrary element of f[S]∪f[T], and show that it necessarily belongs to f[S∪T]. Here’s how that might look in practice:
Let y∈f[S]∪f[T]; then by the definition of union we know that y∈f[S] or y∈f[T]. Suppose first that y∈f[S]; then there is some x∈S such that f(x)=y. Of course S⊆S∪T, so x∈S∪T, and therefore y=f(x)∈f[S∪T].
Now suppose instead that y∈f[T]; then there is some x∈T such that f(x)=y. Of course T⊆S∪T, so x∈S∪T, and therefore y=f(x)∈f[S∪T]. In all cases, therefore, y∈f[S∪T], and since y was an arbitrary member of f[S]∪f[T], it follows that f[S]∪f[T]⊆f[S∪T].
Once you really understand what you’re doing, you can shorten this quite a bit, but at this point, when you’re still feeling your way, it’s better to include too much detail than to include too little.
No comments:
Post a Comment